2021
DOI: 10.1515/shll-2021-2044
|View full text |Cite
|
Sign up to set email alerts
|

Madrileños on theejque: Perceptions of Velarized /s/

Abstract: This paper explores the identities that Madrileños ascribe to speakers using velarized coda /s/. The language attitudes of 59 participants from Madrid were assessed by means of a matched guise survey in which they heard native Madrileños using either sibilant coda /s/ or velarized coda /s/. Results show that while Madrileños do perceive the velarized variant as a marker of a Madrid origin, this effect is mainly observed for female voices. In addition, speakers that used velarized /s/ were associated with more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…As such it is inseparable from the ideological field and can be seen as an embodiment of ideology in linguistic form" (Eckert 2008, p. 464). The multitude of social meanings 8 attached to linguistic variants has been supported by several sociolinguistic perception studies, where the manipulation of a single phonetic variant (Barnes 2015;Campbell-Kibler 2007Chappell 2016Chappell , 2018Chappell , 2019Chappell , 2020Chappell , 2021aRegan 2020Regan , 2022bRegan , 2022cWalker et al 2014;Wright 2021aWright , 2021b or of a single word (Baird et al 2018;Regan 2022a) between guises affects listeners' evaluations. Other sociolinguistic perception studies have examined the indexical fields of language varieties 9 (Callesano and Carter 2019;Carter and Callesano 2018;Chappell and Barnes 2023;Niedzielski and Preston 1999), demonstrating that speech perception research can further our understanding of the social meaning of language varieties as well.…”
Section: Social Information In Speech Perceptionmentioning
confidence: 97%
See 1 more Smart Citation
“…As such it is inseparable from the ideological field and can be seen as an embodiment of ideology in linguistic form" (Eckert 2008, p. 464). The multitude of social meanings 8 attached to linguistic variants has been supported by several sociolinguistic perception studies, where the manipulation of a single phonetic variant (Barnes 2015;Campbell-Kibler 2007Chappell 2016Chappell , 2018Chappell , 2019Chappell , 2020Chappell , 2021aRegan 2020Regan , 2022bRegan , 2022cWalker et al 2014;Wright 2021aWright , 2021b or of a single word (Baird et al 2018;Regan 2022a) between guises affects listeners' evaluations. Other sociolinguistic perception studies have examined the indexical fields of language varieties 9 (Callesano and Carter 2019;Carter and Callesano 2018;Chappell and Barnes 2023;Niedzielski and Preston 1999), demonstrating that speech perception research can further our understanding of the social meaning of language varieties as well.…”
Section: Social Information In Speech Perceptionmentioning
confidence: 97%
“…Speech perception studies have been fundamental to understanding the social meaning 1 of linguistic variation and language varieties. It has been shown that linguistic information affects social perceptions of speakers (Barnes 2015;Campbell-Kibler 2007;Chappell 2016;Regan 2022c;Walker et al 2014;Wright 2021a) and that social information affects linguistic perception as well (Barnes 2019;Hay et al 2006aHay et al , 2006bHay and Drager 2010;Koops et al 2008;Niedzielski 1999). For example, subtle differences in linguistic information, 2 such as hearing affricate [t ] or fricative [ ] for the voiceless prepalatal /t / in Andalusian Spanish (Regan 2020), can affect the social perception 3 of the speaker.…”
Section: Introductionmentioning
confidence: 99%